The Influence of Leadership Style, Workload and Work Discipline on Employee Productivity RKM Ahmad Yani Branch - Permana Putra, Reynaldi; Chandra Jaya, Rama (Dinasti Publisher, 2024)
The purpose of this study is to determine the effect of leadership style, workload and work discipline on the productivity of Employees at the Building Store of Ahmad Yani Branch, both partially and simultaneously. The population in this study was all employees at the Ahmad Yani branch of RKM building store, with a total of 40 employees. SampWork Environmental Engineering used in this study is a non-probability Work Environmental technique. The method used in this study is Quantitative Method with data collection techniques used is interview and distribute questionnaires to respondents. The data analysis technique used is double linear regression with SPSS program. The results of the study concluded that: (1) the dreaming style has a significant positive effect on productivity. (2) the workload has a significant effect on productivity. (3) the work discipline has a positive and significant effect on productivity. (4) In simultaneous testing of leadership styles, workloads and work discipline have a positive and significant influence on employee productivity in the building store of Ahmad Yani branch. The magnitude of leadership style, workload and Work Discipline is shown by the Adjustable R Field value of 79.9% and the remaining 21.1% are affected by other variables not examined in the study.